Establishment of Seed Production Area of Amla (Emblica officinalis Gaertn.) in Punjab - Luna, R. K. (Indian Forester, 2005)
Emblica officinalis is an important multipurpose tree grown by farmers and Forest departments. Establishment of seed production area (SPA) is considered as the first step towards tree improvement programme for production of qualitative seed at a moderate cost. This is the first report about establishment of SPA of Emblica officinalis in India. Methodology to establish SPA of Amla using point grade method considering quantitative and qualitative traits notably crown and fruiting characters of the tree has been described in this article. The population achieved a gain of 10.61% to 17.87% in crown and 17.07% to 25.97% in fruiting trait in the first and second culling respectively. The total seed production capacity per annum of the SPA has been calculated to be 177.2 kg and 158.08 kg after first and second culling respectively, which will be sufficient to afforest 3700 ha of area.